Two new compounds from Carpesium abrotanoides. (December 2020) - Qian, Qun-Gang; Gong, Li-Min; Yang, Shen-Hui; Zhao, Bi-Qing; Cai, Jia; Zhang, Zheng-Jie; Wang, Yue-Hu; Zhou, Xiao-Jiang
Graphical abstract: Highlights: Two new compounds were isolated from herbal material of Carpesium abrotanoides L. The structures of 1 and 2 were elucidated by single-crystal X-ray diffraction analysis and ECD calculation. Compound 1 showed moderate cytotoxicity against tumor cells with IC50 values ranging from 11.46 to 23.68 μM. Abstract: Two new compounds, named carpabrotalactone C (1 ) and methyl 8-[2(5 H )-furanon-5-yl]octanoate (2 ), were isolated from the herbs of Carpesium abrotanoides L. The structures of these compounds were elucidated based on spectroscopic analysis, single crystal X-ray diffraction analysis and ECD calculation. Compound 1 exhibited potent cytotoxicity against the A549, SMMC-7721, MCF-7 and SW480 cell lines, with IC50 values from 11.46 to 23.68 μM. Meantime, compound 1 showed weak inhibitory eﬀ ;ects on LPS-induced NO release in RAW 264.7 cell lines, with IC50 value of 63.23 ± 2.55 μM.